'n Ondersoek na die aanwending van mikrorekenaarstelsels in klein sakeondernemings in Suid-Afrika - P. J.S. Bruwer; C. E. Pretorius (South African Journal of Business Management, 1986)
– An investigation into the use of microcomputer systems in small businesses in South Africa The relatively low cost and great advantages, i.e. accuracy, time and cost savings, better decision making, more professional service to clients, etc. make a microcomputer system an attractive aid for any business and particularly for the small business. This is why microcomputers will, today and in future, play an ever-increasing role in the business world. The implementation of a microcomputer system, however, implies major changes for the business and these changes may create major problems for the management of the small business. The objectives of this research project are to determine the extent to which microcomputer systems are used in small businesses in South Africa, what problems they experience with these systems, and to suggest possible solutions to these problems. Furthermore, the major contributing factors to the successful application of microcomputer systems in small businesses are identified by using regression techniques.
Keywords: 650